Overview of Psychiatric Emergencies in Primary Health Care Centers - Pragholapati, Andria; Fitrikasari, Alifiati; Handayani, Fitria (Global Health Science Group, 2024)
This research aims to provide an overview of psychiatric emergencies in Primary Health Care Centers (Puskesmas), focusing on the identification of psychiatric emergency cases, initial interventions provided by healthcare professionals at Puskesmas, and the collaboration between Puskesmas and the nearest hospital's psychiatric unit. The research utilized a descriptive approach, collecting data through interviews with healthcare personnel at Puskesmas, direct observations, and analysis of medical records. Results of the research reveal that psychiatric emergencies at Puskesmas encompass various conditions such as acute mental disorders, severe anxiety, and the risk of harmful behaviors. Initial interventions by healthcare professionals at Puskesmas include clinical evaluations, temporary medical interventions, and referrals to the hospital's psychiatric unit if necessary. Collaboration between Puskesmas and the nearest hospital's psychiatric unit was found to be crucial in ensuring the smooth referral process and effective management of psychiatric emergency cases. These findings offer a comprehensive insight into the challenges and opportunities faced in dealing with psychiatric emergencies at the primary care level. The implications of this research can serve as a foundation for enhancing the availability of human resources, facilities, and coordination between Puskesmas and hospital psychiatric units to improve the quality of services for individuals experiencing psychiatric emergencies at the primary care level.